Thermal homogenization of boreal communities in response to climate warming - Mäkinen, Jussi; Ellis, Emilie E; Antão, Laura H; Davrinche, Andréa; Laine, Anna-Liisa; Saastamoinen, Marjo; Conenna, Irene; Hällfors, Maria; Santangeli, Andrea; Kaarlejärvi, Elina; Heliölä, Janne; Huikkonen, Ida-Maria; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2025)
Globally, rising temperatures are increasingly favoring warm-affiliated species. Although changes in community composition are typically measured by the mean temperature affinity of species (the community temperature index, CTI), they may be driven by different processes and accompanied by shifts in the diversity of temperature affinities and breadth of species thermal niches. To resolve the pathways to community warming in Finnish flora and fauna, we examined multidecadal changes in the dominance and diversity of temperature affinities among understory forest plant, freshwater phytoplankton, butterfly, moth, and bird communities. CTI increased for all animal communities, with no change observed for plants or phytoplankton. In addition, the diversity of temperature affinities declined for all groups except butterflies, and this loss was more pronounced for the fastest-warming communities. These changes were driven in animals mainly by a decrease in cold-affiliated species and an increase in warm-affiliated species. In plants and phytoplankton the decline of thermal diversity was driven by declines of both cold- and warm-affiliated species. Plant and moth communities were increasingly dominated by thermal specialist species, and birds by thermal generalists. In general, climate warming outpaced changes in both the mean and diversity of temperature affinities of communities. Our results highlight the complex dynamics underpinning the thermal reorganization of communities across a large spatiotemporal gradient, revealing that extinctions of cold-affiliated species and colonization by warm-affiliated species lag behind changes in ambient temperature, while communities become less thermally diverse. Such changes can have important implications for community structure and ecosystem functioning under accelerating rates of climate change.
Keywords: Phytoplankton; Climate Change; ekosystém; Finsko; biodiverzita; Moths; climate change; globální oteplování; niche position; Birds; klimatické změny; niche breadth; můry; Global Warming; zvířata; Temperature; Finland; fytoplankton; Biodiversity; climatic debt; ptáci; Butterflies; Ecosystem; motýli; teplota; community temperature index; Animals